2016
DOI: 10.13189/ijnbs.2016.040102
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose L-methionine-associated Changes in Behavioural Indices in Young Rats

Abstract: Objective: The study objectives were to investigate the effects of L-methionine (at low doses) on open-field novelty-induced behaviours, anxiety-related behaviours, working-memory and brain S-adenosyl-methionine (SAMe) levels in young rats. This was with a view to determine whether administration of low doses of L-methionine can significantly alter behavioural parameters, working-memory and brain SAMe levels, or not. Methodology: Wistar rats (40-45 g each) were given distilled water or L-methionine (5 and 10 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…The fact that L-MET at the dose of 50 mg/kg was the most effective in suppressing SWDs in WAG/Rij rats and that this effect appeared by the 4th hour after administration confirms previously published data [36]. Our findings concerning the anxiolytic-like effect of L-MET in WAG/Rij rats are consistent with the data of others who have shown an anxiolytic-like effect of low doses (5 and 10 mg/kg) of L-MET treatment comparable to that of diazepam in the elevated plus-maze test in Wistar rats [39]. It should be noted that the anxiolytic and antidepressant-like effects of SAMe have been well-documented previously [39,64,66,69].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The fact that L-MET at the dose of 50 mg/kg was the most effective in suppressing SWDs in WAG/Rij rats and that this effect appeared by the 4th hour after administration confirms previously published data [36]. Our findings concerning the anxiolytic-like effect of L-MET in WAG/Rij rats are consistent with the data of others who have shown an anxiolytic-like effect of low doses (5 and 10 mg/kg) of L-MET treatment comparable to that of diazepam in the elevated plus-maze test in Wistar rats [39]. It should be noted that the anxiolytic and antidepressant-like effects of SAMe have been well-documented previously [39,64,66,69].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, it is not clear whether L-MET can have antiepileptic activity. Several studies focus on the effect of L-MET on locomotor and exploratory activity, anxiety level, memory, and convulsive seizures (kainate model of temporal lobe epilepsy) [39,40]. However, there are no studies of the effects of L-MET on depression associated with absence epilepsy in experimental models of this pathology.…”
Section: Introductionmentioning
confidence: 99%
“…The stimulation of the inhibitory neurotransmitter gamma amino-butyric acid (GABA) receptors has also been associated with locomotor retardation or a central depressant response. Studies have also shown that the activation of A and B subtypes of the GABA receptors reduces grooming frequency (66,69). The result of brain GABA levels in this study also supports the inhibitory response observed, although the rich essential amino acid content of C. mannii (4, 26) could also alter neurotransmitter balance in favour of a central inhibitory response.…”
Section: Cucumeropsis Manniisupporting
confidence: 84%
“…While there is a dearth of scientific studies examining the central nervous system effects of C. mannii, central depressant effects of a given compound or drug have been attributed to their ability to downregulate or upregulate excitatory or inhibitory neurotransmitters respectively. Alterations in horizontal locomotion or grooming in the open field has been associated with changes in the activity of dopamine (DA) in a number of studies (65,66). Methylation at the DA receptors, synaptic cleft or receptor-bound DA (67,68), and inhibition of ligand gating to dopamine also results in a downregulation of DA receptors, resulting in locomotor retardation or a reduction of self-grooming.…”
Section: Cucumeropsis Manniimentioning
confidence: 99%
“…Methionine (Met) is an essential amino acid that plays a vital role in cell metabolism, immune cell production, normal nerve function, growth and development, and many other tissue functions [1][2][3]. At the same time, Met plays an important role in human physiological and pathological processes.…”
Section: Introductionmentioning
confidence: 99%